Reducing mine water contamination at the local drainage facility of a kimberlite mine - N. P. Ovchinnikov (Горные науки и технологии, 2025)
The clarification of contaminated mine water by means of sedimentation in designated water collectors is accompanied by a gradual decrease in their effective volume due to siltation. The operation of pumping units within the drainage facility under conditions of silted water collectors at underground mining site adversely affects both their service life and energy efficiency. To prevent severe degradation in pump operating conditions, silted underground water collectors are regularly taken out of operation for cleaning, using self-propelled equipment. As Russian kimberlite mines reach their design capacity, the interval between cleaning cycles of the local drainage system’s water collectors has significantly decreased. Currently, at kimberlite mines, the cleaning of silted water collectors is routinely carried out using all available load–haul–dump (LHD) machines operated by the mine’s Mechanical and Power Service. The expansion of the LHD fleet is constrained by the high cost of these machines. In this context, reducing the intensity of mine water contamination entering the water collectors of the local drainage system has become a pressing and practically significant objective. Mathematical modeling has shown that a substantial reduction in mine water contamination within the local drainage system of a kimberlite mine can be achieved by eliminating sludge formation caused by ore spillage during transfer from the feeder to the main level conveyor belt. To eliminate this source of sludge formation, a mechanized system for collecting ore spillage has been developed, with a specially designed collecting and loading unit as its key component.